2011
DOI: 10.1016/j.cryobiol.2010.10.159
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mouse oocytes after being cooled in a vitrification solution to −196°C at 95° to 70,000°C/min and warmed at 610° to 118,000°C/min: A new paradigm for cryopreservation by vitrification

Abstract: There is great interest in achieving reproducibly high survivals of mammalian oocytes (especially human) after cryopreservation, but the results to date have not matched the interest. A prime cause of cell death is the formation of more than trace amounts of intracellular ice, and one strategy to avoid it is vitrification. In vitrification procedures, cells are loaded with high concentrations of glass-inducing solutes and cooled to −196°C at rates high enough to presumably induce the glassy state. In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 23 publications
12
113
0
Order By: Relevance
“…Seki and Mazur [13,14] have shown that warming rates are more important than cooling rates for successful cryopreservation. In the slow-freezing program suggested by Testart, fast warming is required.…”
Section: Discussionmentioning
confidence: 99%
“…Seki and Mazur [13,14] have shown that warming rates are more important than cooling rates for successful cryopreservation. In the slow-freezing program suggested by Testart, fast warming is required.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 represents just two examples when the Isachenkos published their paper, and other cryobiologists, who came to the same conclusions, namely: -There is no proof of the absence of vitrification inside the sperm even at quite slow cooling [Morris, 2006]; the role of intracellular ice in the death of fast cooling mouse sperm is also questioned in [Mazur & Koshimoto, 2002]. -Some cells can be vitrified in "diluted" solutions at relatively slow rate of cooling but very fast warming is essential for kinetic VF [Mazur & Seki, 2011] Thus, both cryobiologists have reported similar findings as the Isachenkos observations, but they unfortunately fell short of mentioning Isachenkos in their own publications and presentations (e.g., in Cryo-2010 in Bristol), which might have made looking their observations (that were solid, of course) for an unfamiliar reader as "pioneering" or even as "a new paradigm for cryopreservation by vitrifcation" [Mazur & Seki, 2011] ].…”
Section: A Turn Of the Helix: The Isachenkos' Experiments On Vitrificmentioning
confidence: 98%
“…With this method, rapid cooling and rapid warming (especially rapid warming) prevent intracellular ice from forming and recrystallizing [22,23], thus increasing the survival of cells in which dehydration and permeation by cryoprotectants are insufficient. Therefore, this method is effective for cells that have low membrane-permeability.…”
Section: Development Of Vitrified Mouse Oocytes Expressing Aqp3mentioning
confidence: 99%